2015
DOI: 10.1155/2015/189232
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Artemisinin-Based Combination Therapy for the Treatment of Uncomplicated Malaria: A Systematic Review and Meta-Analysis

Abstract: Adherence to artemisinin-based combination therapy (ACT) is not clearly defined. This meta-analysis determines the prevalence and predictors of adherence to ACT. Twenty-five studies and six substudies met the inclusion criteria. The prevalence of ACT adherence in the public sector was significantly higher compared to retail sector (76% and 45%, resp., P < 0.0001). However, ACT adherence was similar across different ACT dosing regimens and formulations. In metaregression analysis prevalence estimates of adheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 60 publications
3
39
2
Order By: Relevance
“…Of note, to our knowledge, Seasonal Malaria Chemoprevention measures as recommended by the World Health Organization had not been implemented at the time the study ended in any of the study sites [ 35 ]. This finding may be explained by a number of highly interrelated extrinsic environmental, social, and economic factors such as diagnosis confirmation and local treatment practices, care seeking behaviour, access to health facilities and availability of local anti-malarials [ 36 ]. The discrepancy between infection prevalence and infrequent use of anti-malarials at some sites may be related to the immunity afforded by chronic infections resulting in asymptomatic parasite carriage, which have been widely described in P. falciparum endemic areas, including Africa [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, to our knowledge, Seasonal Malaria Chemoprevention measures as recommended by the World Health Organization had not been implemented at the time the study ended in any of the study sites [ 35 ]. This finding may be explained by a number of highly interrelated extrinsic environmental, social, and economic factors such as diagnosis confirmation and local treatment practices, care seeking behaviour, access to health facilities and availability of local anti-malarials [ 36 ]. The discrepancy between infection prevalence and infrequent use of anti-malarials at some sites may be related to the immunity afforded by chronic infections resulting in asymptomatic parasite carriage, which have been widely described in P. falciparum endemic areas, including Africa [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the efficacy of many of the plants used as medicine is scientifically unproven due to insufficient pharmacological research and may interact with prescription medicines [ 33 ] Thirdly, the knowledge of the medicinal plants and their uses is passed from one generation to another orally and is not documented hence is at risk of distortion and loss [ 33 ]. Lastly, use of traditional medicines simultaneously with conventional malaria medicine may lead to non-compliance to biomedical treatment resulting in sub-optimal parasitological and clinical outcomes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the large sample size in our study likely led to finding statistically significant relationships with low effect estimates 36,37 ; however, our estimates of determinants of adherence were consistent with other MDA studies and help characterize adherent from nonadherent individuals in this trial. 38 In the context of a community-randomized controlled trial in Southern Province, Zambia, community-wide MDA and fMDA with DHAp both demonstrated high treatment adherence and high and durable clearance of malaria infections. Differences in adherence between MDA and fMDA trial arms suggest that the specific strategy for deploying an MDA intervention can influence the reception of treatment.…”
Section: Discussionmentioning
confidence: 99%